Studying ideal temperature for faster carbonation in waste slag: examining thermal effects on CO2 uptake and reaction efficiency - Lee, Jia Jun (2024)
This study explores the potential of Electric Arc Furnace slag for CO2 sequestration by investigating its carbonation behaviour under varying temperatures, humidity levels, and CO2 concentrations. The research aims to optimize CO2 conversion efficiency and assess the stability of the resulting carbonate minerals. Utilizing techniques like X-ray Diffraction, EnergyDispersive X-ray Spectroscopy, Scanning Electron Microscopy, and Thermogravimetric Analysis, the study reveals that carbonation significantly influences the microstructure and mechanical properties of slag-based mortar. Higher temperatures are shown to enhance CO2 uptake and promote the formation of carbonate crystals. The findings highlight EAF slag's potential as a sustainable construction material capable of contributing to CO2 mitigation efforts. The maximum compressive strength recorded was 28.94 kN for concrete made with EAF slag, under conditions of 30°C, 80% humidity, and 20% CO₂ concentration. This research highlights the effectiveness of carbonated steel slag as a sustainable material for concrete production, offering both improved mechanical performance and enhanced carbon sequestration, making it a promising solution for greener construction practices.